A rare case of a migrating fishbone lodged in the larynx for 6 months in a patient with delayed presentation due to COVID-19 pandemic. Issue 5 (17th May 2021) - Alreefi, Mohamed; Althawadi, Noora; Patel, Ankit; Dwivedi, Raghav
Abstract: A foreign body sensation following fishbone ingestion is a common presentation to the Accident and Emergency Department. Simple removal is achieved with acute presentations and accessible locations. The risk of complications increases with delay in seeking medical attention. We report a case of a migratory fishbone lodged in the larynx for 6 months in a patient with delayed presentation due to COVID-19 pandemic